Technological process structure of parts manufacturing of ship diesels in using function-oriented methods of finishing and hardening treatment. (2019) - Kostenko, A.; Mikhaylov, A.; Pichko, N.
Abstract: Features of technological process structure of manufacturing ship diesel parts in using function-oriented methods of finishing and hardening treatment are examined in this article. Technological transformation model is given. General object-oriented model of structure synthesis of function-oriented process is presented. Requirements for the base containing method codification for the use during the synthesis of the structure of function-oriented process, are shown. The structure of technological function-oriented process is acquired.